2014
DOI: 10.1021/am501988s
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Assembly of NiCo2O4Multiple Hierarchical Structures for High-Performance Pseudocapacitors

Abstract: The design and development of nanomaterials has become central to the advancement of pseudocapacitive performance. Many one-dimensional nanostructures (1D NSs), two-dimensional nanostructures (2D NSs), and three-dimensional hierarchical structures (3D HSs) composed of these building blocks have been synthesized as pseudocapacitive materials via different methods. However, due to the unclear assembly mechanism of these NSs, reports of HSs simultaneously assembled from two or more types of NSs are rare. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…Reproduced with permission. [ 75 ] Copyright 2014, American Chemical Society. [ 70 ] Copyright 2013, Royal Society of Chemistry.…”
Section: Synthesis Of Nico 2 O 4 Nanostructuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 75 ] Copyright 2014, American Chemical Society. [ 70 ] Copyright 2013, Royal Society of Chemistry.…”
Section: Synthesis Of Nico 2 O 4 Nanostructuresmentioning
confidence: 99%
“…[ 1,17,52,53,75 ] By a simple hydrothermal route without templates, Shen and co-workers fabricated NiCo 2 O 4 urchins with a large surface area of 99.3 m 2 g −1 .…”
Section: Synthesis Of Nico 2 O 4 Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [125] reported that the NiCo 2 O 4 multiple hierarchical structures (MHSs) composed of two-dimensional (2D) nanosheets and onedimensional (1D) nanowires were directly anchored on Ni foam (Fig. 6a).…”
Section: Nickel Cobalt Oxidesmentioning
confidence: 99%
“…People are also trying to combine a battery and a supercapacitor to make a hybrid device which will provide both high power density as well as high energy density. Depending on the working procedure supercapacitor is mainly two types-(a) Electric Double Layer Capacitor (EDLC) (Wang and Zhang, 2012;Sharma and Bhatti, 2010) and (b) Pseudocapacitor (Augustyn et al, 2014;Simon and Gogotsi, 2008;Huang et al, 2013;Zhou et al, 2014). EDLC is a non-faradic electrochemical capacitor i.e., no transfer of charge occurs between electrode and electrolyte.…”
Section: Introductionmentioning
confidence: 99%